Records and redescription of a mygalomorph spider genus ignored for over 100 years with a new species: the genus Atmetochilus Simon, 1887 (Araneae, Nemesiidae) in Thailand - Kunsete, Chawakorn; Sivayyapram, Varat; Traiyasut, Prapun; Thanoosing, Chawatat; Khamwan, Kitiwat; Warrit, Natapot (Zootaxa, 2020)
The wishbone spider of genus Atmetochilus Simon, 1887 (Nemesiidae: Bemmerinae) containing six species and is known from Asia. We describe a new Thai species, Atmetochilus songsangchotei sp. nov. Since the holotype of the type species of Atmetochilus, A. fossor, is presumed lost, we describe fresh specimens (ARA-2018-132) and designate one as as neotype; similarly, because a holotype (only syntypes) of Atmetochilus atriceps in NHMUK was not designated, we chose the most intact specimen of the syntypes (NHMUK 1895.9.21.16) and designate it as lectotype. From a photo of the type specimen of Atmetochilus bifidus (sternum) from ZSI, we transfer Atmetochilus bifidus back to Damarchus.